Multi-objective optimization of clinching joints quality using Grey-based Taguchi method - Eshteyah, Mohanna; Hrairi, Meftah (Springer London, 2016)
Clinching joint quality and functionality may have undesirable features because of the choice of the forming process parameters. In fact, there are different factors controlling the mechanical connection strength such as the tools’ geometry and the joint final shape. This paper presents the implementation of the Taguchi-based Grey optimization of the mechanical clinching with fixed dies for dissimilar materials (Aluminum alloy 7075 and Mild Steel) to derive the optimal process parameters combination that leads to a high strength connection subjected to multiple characteristics, namely, the bottom thickness, the interlock length, and the neck thickness of the joint. LS-DYNA explicit and implicit finite element (FE) software was used to simulate the process in order to evaluate the joint strength by loading the sheets vertically. Taguchi’s L27 orthogonal array design and the notion of signal-to-noise (S/N) ratio were utilized to obtain the objective function. Analysis of variance (ANOVA) showed the importance of factors on overall output. The output of the study provided the optimal geometrical parameters of the punch, die, and blank holder. Indeed, the die groove height, die diameter, punch diameter, punch corner radius, and clearance between punch and blank holder were found to be the most influential parameters on the bottom and neck thicknesses. In addition, the output indicated that when bottom thickness or neck thickness increased, the interlock decreased.